A Bibliometric Analysis of Graph Labeling Study Using VOSviewer - Kuan, Yoong Kooi; Azahri, Khairul Azri; Rijal, Muhammad Wirawan Nabil Budiman; Mazlan, Muhammad Imran (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
Graph labeling is a well-known theme of graph theory that involves an assignment of integers to the domain elements such as vertices or edges, or both, subject to certain conditions. A bibliometric and descriptive quantitative approach is used in this study to conduct a bibliometric analysis on graph labeling by integrating mapping analysis with VOSviewer software. The data was obtained from a Google Scholar search using the keyword "graph labeling" that resulted in 980 articles published between 2018 and 2023, but only 375 of these articles were relevant to the subject. The results show that research on graph labeling changed from 2018 to 2023. To sum up, this work is the first to use VOSviewer for bibliometric analysis of a graph labeling study. It is hoped that this will make it a useful resource for future research on related issues.